Sociophonetic Study of Nepali Spoken by the Magar Community in Baglung - Chalise, Krishna Prasad (Gipan, 2024)
This research is a sociophonetic study of the ethnic variety of Nepali spoken by the Magar community in Baglung as their mother tongue. It is unknown which Magar group they belong to and which Magar language their ancestral language was. Data were collected from one male and one female subject at the three research locations. For the F1×F2 plot, the vowels were recorded in the plosive-vowel-plosive environment in disyllabic words, and the pattern of sound change from the standard colloquial Nepali and the Magar variety of Nepali is based on the recorded texts from the speakers. The vowels, in this variety, are relatively neutralized than in the standard colloquial Nepali. Laryngealization of the vowels is a common phenomenon and there is a relatively lower pitch in the speech. The plosives and affricates contrast only in three places of articulation. There is a heavy plosive weakening due to spirantization, desperation, and deaf frication. Regular patterns of sound change from the standard colloquial Nepali to Magar Nepali can be well formulated. In comparison, we find that its sound system is highly influenced by the sound system of Magar. The features found in the speech sounds of this variety justify that it is a well-defined distinct ethnic variety of Nepali.